Seed interferon imbibition leads seedling growth enhancement accompanying by increase in superoxide dismutase activity - Sakhno, L.O. (Фактори експериментальної еволюції організмів, 2014)
Aim. We studied canola (Brassica napus cv Lega) in vitro seedling growth after seed imbibition by human recombinant interferon alpha 2b (INF) produced in bacteria. Methods. Germination, seedling fresh weight (FW), total soluble protein (TSP), and superoxide dismutase activity (SOD) measurements were conducted. Results. INF applications did not improve canola seed germination. TSP was not affected in cotyledons and decreased in hypocotyls. Seedling FW was increased by 100% (10² IU/ml INF), 140% (10³ IU/ml INF), and 70% (10⁴ IU/ml INF) in comparison with controls (treatments by pure water, or INF after boiling, or INF with diethyldithiocarbamate) under growth in thermostat at 24°. Differences in seedling FW were due to differences in hypocotyl and root FWs. SOD activity increased up to 2.18-fold in cotyledons and 1.47-fold in hypocotyls. Conclusions. Human recombinant INF alpha 2b application caused an dose-dependent increase of canola seedling biomass (up to 2.4-fold) during in vitro growth. SOD activity rise and its positive correlation to FW accumulation were detected in these seedlings. We suppose SOD activity increment which occurred due to seed INF imbibition improved plant growth.

Key words: canola, fresh weight, interferon, superoxide dismutase activity.